Vive l'été 2 - De Lepeleire, Damien; Bayer, Céline; Pearson, Laura; Galerie Olivier Biltereyst, Brussel (Brussel : Galerie Olivier Biltereyst, 2014)
Bayer, Céline ; Pearson, Laura ; Kowalski, Stéphanie ; Biltereyst, Olivier ; Bouchat, Laurent ; Carpenter, Patrick ; Odieu, Didier ; Renoux, Philippe ; Bernier, Pascal ; Estève, Lionel ; Mahéo, Erwan ; Noiret-Thomé, Xavier
Vive l'été 2, Galerie Olivier Biltereyst / Librarie Laurent Bouchat, Brussel, June 21 until July 26, 2014
boek